Life of Pi : a novel - Martel, Yann (Canongate, 2012)
After the sinking of a cargo ship, a solitary lifeboat remains bobbing on the wild blue Pacific. The only survivors from the wreck are a sixteen-year-old boy named Pi, a hyena, a wounded zebra, an orangutan, and a 450-pound Royal Bengal tiger.